LITERARY HISTORIOGRAPHY AND THE PROBLEM OF THE AUTHOR: MIHAI IOVĂNEL’S “HISTORY” AND RECENT DEVELOPMENTS IN AUTHORSHIP STUDIES - CIOROGAR, Alex (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Literary Historiography and the Problem of the Author: Mihai Iovănel’s History and Recent Developments in Authorship Studies. The present paper examines the dynamics between literary historiography and authorship studies and the way in which these problems related to Mihai Iovănel’s recent History. Ciorogar argues that authorship theories have always determined the workings of canonicity. Furthermore, the metamorphoses of literary histories could be viewed, he insists, as a series of conceptual revolutions. Consequently, arguments related to authorship have given rise to both new fields of research and disciplines. Finally, Ciorogar also suggests that the evolution of literary criticism and theory is more or less coeval with the history of auctorial models. Article history: Received 26 July 2022; Revised 22 August 2022; Accepted 31 August 2022; Available online 20 September 2022; Available print 30 September 2022. REZUMAT. Istoriografia literară și problema autorului: Istoria lui Mihai Iovănel și noi dezvoltări în studiile de auctorialitate. Lucrarea de față examinează dinamica relațiilor dintre istoriografia literară și studiile de auctorialitate, precum și modul în care aceste două problemă se raportează la recenta Istorie publicată de Mihai Iovănel. Teza principală e aceea conform căreia teoriile auctoriale ar determina modurile de funcționare a canonicității. Mai mult, metamorfozele istoriilor literare ar putea fi privite ca o serie de revoluții conceptuale. În consecință, argumentele și dezbaterile centrate în jurul conceptului de autor au dat naștere atât unor noi domenii de cercetare, cât și altor discipline. În cele din urmă, textul sugerează că evoluția criticii și a teoriei literare reprezintă, astfel, istoria modelelor auctoriale. Cuvinte-cheie: teorii auctoriale, istorie literară, critică și teorie, moartea și revenirea autorului, metodologii de cercetare, Mihai Iovănel